CITIZENS’ RIGHTS AND OBLIGATIONS UNDER ISLAMIC LAW (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
In the article, provides a detailed exploration of the rights and obligations of citizens under Islamic law. It discusses fundamental rights such as the right to life, justice, religious freedom, property ownership, education, fair wages, and participation in governance. Additionally, it highlights obligations, including adherence to laws, payment of zakat, upholding justice, maintaining peace, and respecting others' rights. The article also emphasizes the role of consultation (Shura) in governance, historical examples of religious tolerance, and modern applications of Islamic principles in governance and society. It concludes by underscoring the balance between rights and responsibilities that contribute to justice, social harmony, and moral integrity in an Islamic framework.